Analisis Kandungan Kimia dan Mikrobiologi Kerupuk Kamplang Ikan Tuna Di Desa Momojiu Pulau Morotai - Rinto Muhammad Nur; Iswandi Wahab; Albu Seba (Musamus Fisheries and Marine Journal, 2021)
Crackers are one form of small food that most Indonesians have long known. As well as variants in side dishes, crackers can be eaten as exciting foods. Kamplang crackers are produced from sago flour and fish as a local food product. This study aimed to examine tuna crackers' chemical content and the total plate count (TPC). This study was conducted at the Faculty of Fisheries and Marine Sciences Laboratory, Universitas Pasifik Morotai. This research began with the development of bean media tauge extract agar (TEA) extract, measuring the quality of water, protein content, and ALT cracker kamplang tuna fish. The findings showed 4 percent of the water content of crackers and 58.37 percent of protein. The number of colonies of bacteria <25, so it is not used in calculations. This number of microbes complies with SNI 01-2332.3:2006 in tuna crackers.